2013
DOI: 10.1007/s00520-013-2007-0
|View full text |Cite
|
Sign up to set email alerts
|

Orphan symptoms in advanced cancer patients followed at home

Abstract: Orphan symptoms are rarely assessed, particularly at home. The aim of this multicenter prospective study was to assess the prevalence of these symptoms and eventual factors possibly associated in advanced cancer patients at admission of a home care program. A prospective study was performed at three home care programs in Italy. Patients' data were collected, including age, sex, diagnosis, and Karnofsky status. Possible contributing factors were analyzed; preexisting neurological diseases, cerebral metastases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
2
6
0
1
Order By: Relevance
“…In end-stage cancer patients with a prognosis of approximately one month, the incidence of sialadenitis was found to be 2.9%. A past study reported the following incidences of rare symptoms in home care patients with advanced cancer: 0.3% for myoclonus, 5% for diaphoresis, 2% for tenesmus, 4% for pruritus, and 4% for hiccups, 3 which are comparable with that of sialadenitis in the present study. Although sialadenitis is a rare complication compared with major physical symptoms such as pain and breathing problems, its onset is often accompanied by increasing physical suffering as shown in the present study, in which pain was experienced by 86% of the patients and fever by 62%.…”
Section: Discussionsupporting
confidence: 88%
“…In end-stage cancer patients with a prognosis of approximately one month, the incidence of sialadenitis was found to be 2.9%. A past study reported the following incidences of rare symptoms in home care patients with advanced cancer: 0.3% for myoclonus, 5% for diaphoresis, 2% for tenesmus, 4% for pruritus, and 4% for hiccups, 3 which are comparable with that of sialadenitis in the present study. Although sialadenitis is a rare complication compared with major physical symptoms such as pain and breathing problems, its onset is often accompanied by increasing physical suffering as shown in the present study, in which pain was experienced by 86% of the patients and fever by 62%.…”
Section: Discussionsupporting
confidence: 88%
“…The debates about the characteristics and how to define palliative sedation are reflected in the wideranging prevalence of the practice observed in the literature (1%-88%), [8][9][10]13 which can be attributed to a number of factors: • Different health care settings Higher prevalence in inpatient acute tertiary palliative care units compared with home-care hospice programs 33,34 • Different case mixes in similar settings…”
Section: Prevalence and Settingsmentioning
confidence: 99%
“…14,15 In home-care hospice programs, palliative sedation may be a feasible option. Mercadante et al 37 reported that 13.2% of patients with cancer were sedated in their homes.…”
Section: Prevalence and Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the symptoms examined have a low prevalence in advanced cancer patients admitted to home care, the distress for patients may be high and deserve further analyses. Given the low prevalence of these symptoms, large studies are needed to find possible associated factors [25,26]. The future home care research agenda includes the prevalence of breakthrough dyspnea, the prevalence of oral symptoms and sleep disturbances at home, of which data are in existent.…”
Section: Home Carementioning
confidence: 99%